Legal risk and compliance risk in the banking industry in South Africa - Terblanché, Janet René (North-West University, 2013)
The Basel Committee on Banking Supervision has defined operational risk, legal risk and compliance risk. However, the definitions might not be adequate for countries with a hybrid legal system, such as South Africa. This study aims to provide a practical solution to the problems faced by countries with a hybrid legal system wishing to comply with the Basel Committee’s standards. It is argued that compliance, compliance risk and regulatory risk should all be viewed as constituent components of legal risk, and in turn necessarily also of operational risk in a hybrid legal system. Legal risk is a wide concept which includes all aspects of a legal system, while compliance risk is a narrower concept which only includes the codified aspects of a legal system. Legal risk therefore includes compliance risk. However, the opposite is not true as compliance risk does not include legal risk, and the two concepts are decidedly shown not to be synonymous in a mixed legal system.
Keywords: Basel Committee; Compliance; Compliance risk; Legal compliance; Legal risk; Operational risk; Regulatory compliance; Regulatory risk

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations